Cultural Foundations of Chinese Education. - Gu, Mingyuan (Brill's series on Chinese education., 2013)
Cultural Foundations of Chinese Education describes the evolution of Chinese education for more than 5,000 years, and analyzes in depth its interaction with Chinese culture.